Voleibol escolar: uma proposta de ensino nas dimensões conceitual, procedimental e atitudinal do conteúdo - Barroso, André Luís Rugiero [UNESP]; Darido, Suraya Cristina [UNESP] (Escola de Educação Física e Esporte da Universidade de São Paulo, 2010)
The objective of this study was to build, implement and evaluate a proposal to teaching of volleyball in the three dimensions of content: concept, procedure and attitude. For the development of the present work it was used the method of search-action. Eight meetings were held with the participation of four teachers. The results obtained were discussed in the perspective of working conditions, in the reasons and contents of teaching the sport (volleyball), technology and sports performance, in the dimensions of the content and features, expectations and participation of students. It was found that, in some schools, the working conditions, in relation to the physical space, the available material, the under evaluation of the Physical Education or even the suspicion of other teachers and supervisors, present themselves as obstacles to the development of this component curriculum. However, it was observed that the teachers participating successfully develop a quality education, contributing to rebuilding importance of Physical Education in the environment of formal education. It was confirmed the possibility of developing contents that may go beyond procedure dimension, facilitating the approach of the dimensions concept and attitude of volleyball. Moreover, it was for the effective participation of students, but it has only been due to the provision of teachers in structuring as appropriate their classes, studying, intended time for preparation of activities and offering diverse strategies that stimulated the involvement of students

O objetivo deste estudo foi construir, implementar e avaliar uma proposta de ensino do voleibol nas três dimensões do conteúdo: conceitual, procedimental e atitudinal. Para o desenvolvimento da pesquisa foi utilizado o método da pesquisa-ação, sendo realizados oito encontros, havendo a participação de quatro professores. Os resultados obtidos foram discutidos na perspectiva das condições de trabalho, em por que e para que ensinar esporte (voleibol), na técnica esportiva e rendimento, nas dimensões do conteúdo e nas características, expectativas e na participação dos alunos. Verificou-se que em determinadas escolas as condições de trabalho, seja em relação ao espaço físico, ao material disponível, à desvalorização da Educação Física ou mesmo à desconfiança por parte dos professores de outras áreas e da direção, apresentam-se como obstáculos para o desenvolvimento desse componente curricular. Entretanto, observou-se que os professores participantes conseguiram desenvolver um ensino de qualidade, contribuindo para o redimensionamento da importância da Educação Física no ambiente formal de ensino. Confirmou-se a possibilidade de desenvolvimento de aulas que possam ir além da dimensão procedimental, facilitando a abordagem das dimensões conceituais e atitudinais do voleibol. Além disso, constatou-se uma participação efetiva dos alunos, mas isso somente se deu devido à disposição dos professores em estruturarem de forma apropriada as suas aulas estudando, destinando tempo para elaboração das atividades e oferecendo estratégias diversificadas que estimulassem o envolvimento dos alunos
School volleyball: a proposal to teaching in the dimensions concept, procedure and attitude of content
Keywords: Physical education; School; Pedagogy of sports; Search-action; Volleyball; Educação física; Escola; Pedagogia do esporte; Pesquisa-ação; Voleibol